NADPH Oxidase and Epidermal Growth Factor Receptor Are Promising Targets of Phytochemicals for Ultraviolet-Induced Skin Carcinogenesis - Min Jeong Kim; Su Jeong Ha; Bo Ram So; Chang-Kil Kim; Kyung-Min Kim; Sung Keun Jung (MDPI AG, 2021)
The skin acts as the primary defense organ that protects the body from the external environment. Skin cancer is one of the most common cancers in the world. Skin carcinogenesis is usually caused by cell degeneration due to exposure to ultraviolet (UV) radiation, which causes changes in various signaling networks, disrupting the homeostasis of single skin cells. In this review, we summarize the roles of nicotinamide adenine dinucleotide phosphate oxidase (NOX) and epidermal growth factor receptor (EGFR) in UV-induced skin carcinogenesis. Furthermore, we describe the crosstalk that exists between NOX, EGFR, and protein tyrosine phosphatase κ and its oncogenic downstream signaling pathways. Chemoprevention is the use of chemical compounds to recover the healthy status of the skin or delay cancer development. Current evidence from in vitro and in vivo studies on chemopreventive phytochemicals that target NOX, EGFR, or both, as major regulators of skin carcinogenesis will also be discussed.